Respuesta :
Given y = 3x + 6, we find the x-intercept by setting y = 0 and solving the resulting equation for x: 0 = 3x + 6, or 3x = -6, or x = -2. The x - intercept is (-2,0).
Find the y-intercept by setting x = 0: y = 3(0) + 6 = 6. The y-int. is (0,6).
y = 3x + 6 slope intercept form
change to standard form
-3x + y = 6
to find x-intercept substitute y for zero
-3x + 0 = 6
-3x/-3 = 6/-3
x = -2 so the x-intercept is -2
-3x + y = 6
to find y-intercept substitute x for zero
-3(0) + y = 6
0 + y = 6
y = 6 so the y-intercept is 6
also in y= mx + b (the slope intercept form) b represents the y-intercept.
y = 3x + 6 b is the 6 so 6 is the y-intercept
The ordered pairs: y-intercept (0,6) x-intercept (-2,0)